2015
DOI: 10.12657/folmal.023.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Bulinus snails – intermediate hosts of schistosomes in Ogun State, South-western Nigeria

Abstract: Freshwater snails of the genus Bulinus O. F. Müller, 1781 are intermediate hosts for schistosomes, trematode parasites which cause schistosomiasis. The genus includes closely related species complexes with restricted gene flow between populations of each taxon. Despite their importance as intermediate hosts, unambiguous identification of these snails remains challenging. We applied molecular approach to their identification to achieve a better understanding of the epidemiology of schistosomiasis in an endemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These biomarkers of infection due to S . haematobium are known to correlate with the intensity of infection [ 29 ]. Our study therefore assessed the performance of these urinalysis parameters in the diagnosis of maternal urogenital schistosomiasis in endemic rural communities of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers of infection due to S . haematobium are known to correlate with the intensity of infection [ 29 ]. Our study therefore assessed the performance of these urinalysis parameters in the diagnosis of maternal urogenital schistosomiasis in endemic rural communities of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Snail identification and infection status were done using morphology and molecular methods respectively. Results of the snail identification and infection have been published elsewhere (10).…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies in Southwestern Nigeria have shown that prevalence of schistosome infection among the inhabitants and snail intermediate hosts is high (9,10). The main stay of schistosome treatment in human is paraziquantel-based therapy; while snail control is almost neglected or perhaps they are considered as an accompanying strategy, most especially in high transmission areas (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although molecular biomarkers have played important role in species identification (Stothard, 1996;Hebert et al, 2003;Akinwale et al, 2015), morphological characteristics such as shell and radula structure continue to be the primary means of identification of freshwater snails (Schander and Willassen, 2005). Bulinus globosus and Bulinus jousseaumei are two closely related snails, both of which are intermediate hosts of the parasitic flatworm known to cause schistosomiasis (Salawu and Odaibo, 2012;Stothard et al, 2013;Akinwale et al, 2015;Mkize et al, 2016;Hassan et al, 2016;Chibwana and Nkwengulila, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bulinus globosus and Bulinus jousseaumei are two closely related snails, both of which are intermediate hosts of the parasitic flatworm known to cause schistosomiasis (Salawu and Odaibo, 2012;Stothard et al, 2013;Akinwale et al, 2015;Mkize et al, 2016;Hassan et al, 2016;Chibwana and Nkwengulila, 2017). The study therefore describes the morphological differences in the shell and radula of two snail intermediate hosts of schistosome in South-western Nigeria.…”
Section: Introductionmentioning
confidence: 99%